PENGARUH KUALITAS PELAYANAN, PROMOSI PENJUALAN, DAN LOKASI TERHADAP LOYALITAS NASABAH PADA PT. BANK RAKYAT INDONESIA (PERSERO), TBK UNIT KODYA I PADANG PANJANG - Mega Dezil; Yasri Hasim; Abror Abror (Program Studi Magister Manajemen, 2013)
This research aims to analyze the influence of quality of service (direct evidence and reliability), sales promotions, and location against customer loyalty at PT. Bank Rakyat Indonesia (persero), Tbk Unit Kodya I Padang Panjang. The design of this research is descriptive. Population is customer saving on PT. Bank Rakyat Indonesia (persero), Tbk Unit Kodya I Padang Panjang, which accounts for up to the end of December 2011 as much as 4667 customer. Total sample research 98 customer. The sampling technique used in the study is accidental sampling. Data analysis techniques to test research hypotheses are multiple regression analysis with the F test and test. The results of this study found that the quality of service to ascendant significantly to customer loyalty at PT. Bank Rakyat Indonesia (persero), Tbk Unit Kodya I Padang Panjang with regression coefficients of 0,279, sales promotion effect significantly to customer loyalty at PT. Bank Rakyat Indonesia (persero), Tbk Unit Kodya I Padang Panjang with regression coefficients of 0,249, and location effect significantly to customer loyalty PT. Bank Rakyat Indonesia (persero), Tbk Unit Kodya I Padang Panjang with regression coefficients of 0,349. Key Words : Quality Of Service, Sales Promotion, Location, Customer Loyalty.